What's in a corpus? Utilizing metadata in Latin and Greek text collections - Jovanović, Neven (2007)
For quite a long time now we can use a good number of electronic collections of texts in Latin and ancient Greek. These collections are commercial or not, open-source or not, prepared by specialists or put together by enthusiasts ; but, regardless of their origin and aim, most of such collections share one feature: they are not linguistic corpora sensu stricto, because they do not — and cannot — meet the criteria for linguistic corpus. Accordingly, collections of texts in Latin and Greek seem to be designed — and used — more as libraries or archives than as tools for the study of language. Here I propose some ideas and examples of how to make such collections even more similar to libraries, in order to make them more accessible and searchable, and more widely used.
Zbornik radova bit će objavljen 2008.
Projekt MZOS
ENG